Relevance of Nutrient-Sensing in the Pathogenesis of Trichophyton rubrum and Trichophyton interdigitale - Cruz, Aline H. S.; Santos, Rodrigo S.; Martins, Maíra P.; Peres, Nalu T. A.; Trevisan, Glauce L.; Mendes, Niege S.; Martinez-Rossi, Nilce M.; Rossi, Antonio (Frontiers in Fungal Biology, 2022)
The growth and development of organisms depend on nutrient availability. Dermatophytes must sense nutrient levels and adapt to the host environment to colonize human and animal keratinized tissues. Owing to the clinical importance of the Trichophyton genus, this study compared the expression profile of genes involved in metabolism, cell cycle control, and proteases in two Trichophyton species, Trichophyton rubrum, and Trichophyton interdigitale, in response to nutrients and environmental pH. We also evaluated the activity of enzymes in the tricarboxylic acid, glyoxylate, and methylcitrate cycles. Moreover, the effects of interruption of the transcription factor pacC on T. interdigitale in the same conditions as for the wild-type strain were determined. Our analyses revealed specific responses in each species to nutritional and pH variation. An improved adaptation of T. interdigitale to keratin was observed, compared to that of T. rubrum. T. rubrum growth in buffered keratin media indicated pH 8.0 as an optimal pH condition for metabolic activity, which differed from that for T. interdigitale. Tricarboxylic acid components in T. rubrum showed increased enzymatic activity and transcript accumulation. In T. interdigitale, a higher activity of enzymes in glyoxylate and methylcitrate cycles was observed, with no direct correlation to the transcriptional profile. T. interdigitale fungal metabolism suggests the requirement of anaplerotic pathways in the late cultivation period. The identified differences between T. rubrum and T. interdigitale may represent determinants for adaptation to the host and the incidence of infection with each species.